Flame retardant polyamide 6/nanoclay/intumescent nanocomposite fibers through electrospinning. Issue 10 (June 2014) - Wu, Hao; Krifa, Mourad; Koo, Joseph H
Flame retardant polyamide 6 (nylon 6) nanocomposite nanofibers containing montmorillonite clay (MMT) platelets and intumescent non-halogenated flame retardant (FR) additives were processed by electrospinning. Different methods of mixing nano fillers before electrospinning were explored and compared. It was found that high loadings of nanoclay particles affected the electrospinnability of the nanocomposite material. Good dispersion and exfoliation of nanoclay platelets within individual nanofibers was verified by transmission electron microscopy. The degradation temperature of nanocomposite samples was lower than pristine nylon 6 samples. However the degradation of all nanocomposite formulations was overall slower. Moreover, the difference in residual char weight after decomposition was significant. Microscale combustion calorimeter results show that FR particles played a major role in reducing flammability of the material in both solution- and melt-compounded samples, while MMT nanoclay was effective in improving char residue and in reducing flammability in high-shear melt premixed samples.